Unthinking collaboration : American Nisei in transwar Japan - Buxton, A. Carly (University of Hawaiʹi Press, 2022)
Unthinking Collaboration uncovers the little-known history of Japanese Americans who weathered the years of World War II on Japanese soil. Severed from the country of their birth when the attack on Pearl Harbor abruptly halted all passenger traffic on the Pacific, these Nisei faced the years of total war as members of the Japanese populace, yet as the target of anti-American propaganda and suspicion. Whereas their white American counterparts were sequestered by Japanese authorities, placed on house arrest, or sent home on exchange ships during the war, American Nisei in Japan were left to contribute to the war effort alongside their Japanese neighbors as soldiers, cryptographers, interpreters, and in farming and manufacturing. When the dust of air raid bombings cleared, many such Nisei transitioned into roles in service of the Allied occupation and its goals of democratization and demilitarization. As censors, translators, interpreters, and administrative staff, they played integral roles in facilitating American-Japanese interaction, as well as in shaping policies and public opinion in the postwar era. Weaving archival data with oral histories, personal narratives, material culture, and fiction, Unthinking Collaboration emphasizes the heterogeneity of Japanese immigrant experiences, and sheds light on broader issues of identity, race, and performance of individuals growing up in a bicultural or multicultural context. By distancing "collaboration" from its default elision with moral judgment, and by incorporating contemporary findings from psychology and behavioral science about the power of the subconscious mind to influence human behavior, author A. Carly Buxton offers an alternative approach to history--one that posits historical subjects as deeply embedded in the realities of their physical and discursive environment. Walking beside Nisei as they navigate their everyday lives in transwar Japan, readers "un-think" long-held assumptions about the actions and decisions of individuals as represented in history. The result is an ambitious historical study that speaks to readers who are interested in broader questions of race and trust, empire-building, World War II and its legacy on both the Western and Pacific fronts, and to all who consider questions of loyalty, treason, assimilation, and collaboration